THE ANALYSIS OF KNOWLEDGE MANAGEMENT PROCESS ON SOFTWARE DEVELOPMENT PROCESS: A SYSTEMATIC REVIEW - Ramadhan, Arief; Lila Setiyani (Dinasti Publisher, 2020)
Software quality is affected by its development process. The software development process, in general, goes through several stages, including project management, system requirements analysis, architecture, and design, implementation and testing. On each of these stages it cannot be separated from the process of capturing, storing, transferring and sharing knowledge between the developer and the stakeholders. This systematic review aimed to analyze the knowledge management process in the software development process. In this systematic review we used the Preferred Reporting Item for Systematic Review and Meta-Analysis (PRISMA) guidelines. We reviewed twenty-two works of literature from several publisher sources and analyzed the knowledge management process in software development. The analysis revealed that the knowledge management process has an essential role in improving the quality of software developed. As a conclusion of this systematic review, knowledge management is one of the factors in determining software quality.